PENGEMBANGAN MODUL BERMUATAN NILAI-NILAI KARAKTER DENGAN MODEL INKUIRI UNTUK MATERI FISIKA SUHU DAN KALOR KELAS X - Tita Puspitasari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The purpose of this study is to develop teaching materials in the form of physics modules containing character values using inquiry models in temperature and heat material, according to the 2013 curriculum material. This study was applied in physics learning activities conducted from April to May 2015 at Al High School. Azhar Syifa Budi Jakarta. The method used in this study is the development method. The initial stage of this research was the analysis of teaching material needs, then made the development of physics modules for class X Science which had been validated by several professional high school physics experts and teachers in Jakarta. The instruments used were a needs analysis questionnaire, a validation sheet for physical matter experts, media experts and professional high school physics teachers in Jakarta and a questionnaire for students after using the developed modules. From the results of the validation by the material experts, the average score of the overall aspects was 81%, indicating that the material suitability aspect, the quality of the contents which included the planting of character values and module competency tests were very good. Validation by media experts obtained a percentage of the average score of all aspects of 89%, indicating that the character values outlined in the module are very good as well as aspects of consistency in the module writing format are very good. The results of validation by professional high school physics teachers in Jakarta obtained an average score of 84%, indicating the direction of learning activities that can foster very well-written characters. This physics module can help develop character values in students and can motivate students to learn independently, because this module displays physics concepts through images and is equipped with sentences that lead students to build their knowledge independently. Keywords: Module Development, Inquiry, Temperature and Heat